Determination of the height of the vertical filter for heterogeneous Earth dams with vertical clay core. (13th September 2019) - Salehi-Hafshejani, Saeid; Shayannejad, Mohammad; Samadi-Broujeni, Hossein; Zarraty, Ali-Reza; Soltani, Bahareh; Mohri-Esfahani, Elham; Haeiri-Hamedani, Majedeh; Eslamian, Saeid; Ostad-Ali-Askari, Kaveh
In order to determine the height of the filter in heterogeneous Earth dam, three embankment models were provided in a flume laboratory, with the length of 4.2 m at the base of dam, the width of 60 cm and the height of 1 m and body slope 1H: 2V. In the first model, the fine-grained and coarse-grained soils were used in downstream and upstream of the dam crest respectively. In models 2 and 3 with cutting fine grained soil from the toe of the dam to the dam crest, vertical clay core was replaced. Index of a / L (a thickness of clay core and L is the length of base dam) was 1.7 and 1.10 in the second and third models, respectively. Seepage experiments in tree water height of 80 and 55 and 30 were performed.